The Influence of Economical Prices on Students' Decisions to Purchase Ready-to-Eat Food Around the Campus Environment - Anis Qurnia; Didit Darmawan (Business Management, 2026)
This study aims to analyze the effect of economical prices on the purchasing decisions of fast food by students around the campus area. Fast food is one of the food alternatives widely consumed by students because it is considered practical, affordable, and easy to find. For students, price plays a crucial role in purchasing decision-making considering the limited income and daily financial management needs. A quantitative approach with a literature review method is used in this study to examine the effect of economical fast food prices on students' purchasing decisions around the campus area. The research results were obtained from international and national journal articles on the topic of prices and student consumption behavior. Data analysis was conducted using content analysis techniques to identify patterns and trends in the relationship between economical prices and purchasing decisions. The study results show that economic price is the dominant factor influencing students' purchasing decisions. This research indicates that the more affordable the ready-to-eat food being sold, the higher the likelihood of students making a purchase.